If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + w)(3w + 7) = 0 Reorder the terms: (6 + w)(7 + 3w) = 0 Multiply (6 + w) * (7 + 3w) (6(7 + 3w) + w(7 + 3w)) = 0 ((7 * 6 + 3w * 6) + w(7 + 3w)) = 0 ((42 + 18w) + w(7 + 3w)) = 0 (42 + 18w + (7 * w + 3w * w)) = 0 (42 + 18w + (7w + 3w2)) = 0 Combine like terms: 18w + 7w = 25w (42 + 25w + 3w2) = 0 Solving 42 + 25w + 3w2 = 0 Solving for variable 'w'. Factor a trinomial. (6 + w)(7 + 3w) = 0Subproblem 1
Set the factor '(6 + w)' equal to zero and attempt to solve: Simplifying 6 + w = 0 Solving 6 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + w = 0 + -6 Combine like terms: 6 + -6 = 0 0 + w = 0 + -6 w = 0 + -6 Combine like terms: 0 + -6 = -6 w = -6 Simplifying w = -6Subproblem 2
Set the factor '(7 + 3w)' equal to zero and attempt to solve: Simplifying 7 + 3w = 0 Solving 7 + 3w = 0 Move all terms containing w to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3w = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 3w = 0 + -7 3w = 0 + -7 Combine like terms: 0 + -7 = -7 3w = -7 Divide each side by '3'. w = -2.333333333 Simplifying w = -2.333333333Solution
w = {-6, -2.333333333}
| 3x+8y=9(y+2y+7) | | 13c+51c=-26 | | -11=x+8x+7 | | 5y+5=y(8-2y) | | 13(x-3)-22x=-18 | | v=3.14(3.14)(h) | | x+18+2x=-14-2x-18 | | X+(2x+0.10)=2.5 | | 2x+n=3 | | 95+52a=303 | | y=x^2-11x+20 | | 0.5x+0.4=0.08x-0.5 | | 5b+20=1.75 | | 6x-4=3x-28 | | 3x^2+23=4 | | -3+t=19 | | -4(3x-9)+6(2x+7)= | | 36-(2c+3)=2(c+4)+c | | v=3.14h | | 4y-25=15 | | 7x+8=107-2x | | 9+4x-5=-8 | | 7s^2+48s-7= | | 8+3x=x+2 | | 7+22=33-4 | | -84=7(-5-x) | | 9b+8b-13=106 | | 4x+2=y | | 3(x+5)+2(4x-7)= | | -(4x+6)=40 | | -44=10x-x-1 | | 15-15(-7-11x)=-13(16-19x) |